Diffuse Leukoplakia of the Bladder Ostium-Sparing in Patient Treated with Leuprorelin for Breast Cancer - Antonio Nacchia; Ferdinando di Giacomo; Arcangelo Di Cerbo; Massimo Dante Di Somma; Giuseppe Patitucci; Giuseppe Disabato; Giulia Vita (Case Reports in Urology)
Case. A 55-year-old woman came to our attention in April 2020 referring haematuria, frequency and urgency. The patient referred previous treatment with leuprorelin 3.75 mg/2 ml for breast cancer three years ago. Urine culture was performed and resulted always negative for pathogens. Cystoscopy revealed a whitish plaque lesion on the fundus, dome, trigone, and left lateral wall of the bladder. Histology of the biopsy confirmed the diagnosis of leukoplakia of the bladder. The plan is to follow her up repeating a cystoscopy every three months and biopsy in 6 months. Literature search revealed very little information on pathogenesis and prognosis of this condition due to its rare occurrence. The main objective of our case study was to describe individual situation of a woman affected by diffuse leukoplakia of the bladder ostium-sparing with a previous treatment with leuprorelin 3.75 mg/2 ml for breast cancer and to show safety of follow-up by cystoscopy and biopsy. Conclusions. We showed a case of a woman treated with leuprorelin and with diffuse leukoplakia of the bladder. We support the recommended long-term follow-up and surveillance based on the literature review by cystoscopy with or without biopsy.